2003
DOI: 10.1002/mds.10593
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for Parkinson's disease dissociates mood and motor circuits: A functional MRI case study

Abstract: Behavioral disturbances have been reported with subthalamic (STN) deep brain stimulation (DBS) treatment in Parkinson's disease (PD). We report correlative functional imaging (fMRI) of mood and motor responses induced by successive right and left DBS. A 36-year-old woman with medically refractory PD and a history of clinically remitted depression underwent uncomplicated implantation of bilateral STN DBS. High-frequency stimulation of the left electrode improved motor symptoms. Unexpectedly, right DBS alone eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
152
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 82 publications
11
152
2
3
Order By: Relevance
“…Mood problems are more common in patients treated with STN-DBS than those treated with GPi-DBS Follett et al, 2010;Moro et al, 2010;Bronstein et al, 2011). Although the underlying substrate of these side effects remains to be characterized, it has been suggested that they may be induced by stimulation in non-motor areas of STN or GPi, inadvertent involvement of limbic structures outside of the target regions (Bejjani et al, 1999;Krack and Vercueil, 2001;Kulisevsky et al, 2002;Romito et al, 2002;Herzog et al, 2003a;Okun et al, 2003;Stefurak et al, 2003), and preexisting psychiatric conditions (Lilleeng and Dietrichs, 2008). Although significant unpleasant mood side effects following STN or GPi DBS are relatively rare (Funkiewiez et al, 2004;Castelli et al, 2006;Tir et al, 2007), their occurrence significantly disrupts patients' quality of life.…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Mood problems are more common in patients treated with STN-DBS than those treated with GPi-DBS Follett et al, 2010;Moro et al, 2010;Bronstein et al, 2011). Although the underlying substrate of these side effects remains to be characterized, it has been suggested that they may be induced by stimulation in non-motor areas of STN or GPi, inadvertent involvement of limbic structures outside of the target regions (Bejjani et al, 1999;Krack and Vercueil, 2001;Kulisevsky et al, 2002;Romito et al, 2002;Herzog et al, 2003a;Okun et al, 2003;Stefurak et al, 2003), and preexisting psychiatric conditions (Lilleeng and Dietrichs, 2008). Although significant unpleasant mood side effects following STN or GPi DBS are relatively rare (Funkiewiez et al, 2004;Castelli et al, 2006;Tir et al, 2007), their occurrence significantly disrupts patients' quality of life.…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) mood responses are obtained by stimulation of different parts of the STN in human parkinsonian patients (MacKinnon et al, 2005;Mallet et al, 2002;Stefurak et al, 2003). However, it must be remembered that the relative size of the territories could be different in the two species.…”
Section: Basal Ganglia Functional Subdivisionsmentioning
confidence: 99%
“…The STN and mood Depression, apathy and anxiety can arise as complications after surgery [60][61][62][63] and rare cases of acute stimulationinduced depressed mood have been reported [57,58]. However, the vast majority of cases with an acute emotional response to STN DBS exhibit hypomania [50] or mania [25,52].…”
Section: The Stn and Impulsivitymentioning
confidence: 99%